Mercury extraction from contaminated soils by L-Cysteine: species dependency and transformation processes - Wenke, Anne; Biester, Harald (Water, air & soil pollution, 2011)
A new approach in soil remediation washing techniques is the use of l-cysteine based on the formation of organic complexes. In this study, the applicability of l-cysteine for the mobilisation of different mercury species from contaminated soils was evaluated. Soils were treated with l-cysteine solutions with S-Hg molar ratios of 1, 2, 10, 20, 100 and 200. In 24 h batch experiments, leachates with water could mobilise 1% of Hg. The addition of l-cysteine led to an increase of Hg mobilisation of 42% for soils with inorganically bound Hg. In column experiments, the maximum Hg removal rate was 75%. For soils with organically bound Hg or HgS, only 1-5% of Hg was mobilised. Thus, the extraction of Hg from soils with l-cysteine is highly dependent on the Hg-binding form. Hg speciation analyses of leachates indicate that Hg-l-cysteine complexes are labile complexes which can be easily transformed. Soil samples speciation analysis revealed that reduction to elemental mercury takes place at low S-Hg ratios (1 to 10), assumingly by microbial activity. At higher S-Hg ratios of 10 and 100, precipitation of stable Hg-S complexes could be observed. These species transformation processes are limitations for considering l-cysteine leaching as a remediation strategy.